Effects of magnetic field on the runaway instability of relativistic accretion tori near a rotating black hole. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Karas, V.; Hamerský, J.
Abstract: Runaway instability operates in accretion tori around black holes, where it affects systems close to the critical (cusp overflowing) configuration. The runaway effect depends on the radial profile l ( R ) of the angular momentum distribution of the fluid, on the dimension-less spin a of the central black hole (| a | ≤ 1), and other factors, such as self-gravity. Here we discuss the role of runaway instability within a framework of an axially symmetric model of perfect fluid endowed with a purely toroidal magnetic field.